Application of the Peer Tutor Learning Model to Improve Learning Outcomes of Fifth Grade Students at Cintawana Elementary School in Mixed Integer Computing Operations - Sri Hernawati (Indonesian Journal of Educational Science and Technology, 2023)
The main problem in this study is the low learning outcomes of fifth grade students at SDN Cintawana in solving mixed integer arithmetic operations. The formulation of the problem in this study is: "How can peer tutoring improve learning outcomes for fifth grade students at Cintawana Elementary School in Mixed Integer Computing Operations?". To improve student learning outcomes, the researchers used Peer Tutor Learning to complete mixed integer arithmetic operations. The design of this study refers to the Kemmis and Mc. Taggart which consists of 4 components, namely 1) planning, 2) implementing actions, 3) observation, and 4) reflection. The data collected was in the form of teacher and student activity data during the learning process obtained using observation sheets, field note data, data from interviews with several students, student learning outcomes data obtained by giving individual tests to students as well as self-assessment sheets, attitudes and interest. The overall results can be seen from the percentage of classical learning completeness in cycle I which only reached 74.30% then in cycle II, the percentage of classical learning completeness reached 84.71%. The results of observations, research attitudes and interests on average are in the good category.